2016
DOI: 10.1073/pnas.1610688113
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the He 2 quantum halo state using a free electron laser

Abstract: Quantum tunneling is a ubiquitous phenomenon in nature and crucial for many technological applications. It allows quantum particles to reach regions in space which are energetically not accessible according to classical mechanics. In this "tunneling region," the particle density is known to decay exponentially. This behavior is universal across all energy scales from nuclear physics to chemistry and solid state systems. Although typically only a small fraction of a particle wavefunction extends into the tunnel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 35 publications
3
95
0
4
Order By: Relevance
“…rived from a nanosieve transmission experiment [13]. The value D 0 =151.9±13.3 neV, obtained very recently [14] using the Coulomb explosion technique, agrees with our theoretical prediction within 0.98 σ.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…rived from a nanosieve transmission experiment [13]. The value D 0 =151.9±13.3 neV, obtained very recently [14] using the Coulomb explosion technique, agrees with our theoretical prediction within 0.98 σ.…”
supporting
confidence: 86%
“…The dimer composed of 4 He atoms, 4 He 2 , has a single very weakly bound vibrational state-an example of a quantum halo state-where atoms move mainly in the classically forbidden tunneling region of the configuration space [8]. This state was the subject of several experimental investigations [9][10][11][12][13][14]. We present here the development of a new potential with uncertainties reduced by an order of magnitude compared to the previous most accurate determination [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here specific molecular dynamics are initiated via tailored transient excitations, such as charge transfer, vibrational excitation, the creation of a valence hole via ionization, or the creation of non-equilibrium Rydberg wavepackets. Recent experiments highlight the promising opportunities for dynamic reaction microscope studies at high repetition rate XFELs [34][35][36][37]. For example, LCLS experiments at 120 Hz by Erk et al on charge-transfer processes in gas-phase iodomethane [33] identified three dissociative channels based on the time-dependent kinetic energy distributions of the charged fragments (Figure 9 right).…”
Section: Energy and Charge Dynamics In Atoms And Moleculesmentioning
confidence: 99%
“…A direct measurement of the Efimov trimer energies and also the heliumdimer wave function [11] shows that a new aspect in few-body physics would be interesting to be studied in experiments: how the effective spatial dimension in atomic traps influence the observables related to Efimov physics. The question of dimensionality is frequently explored in the context of many atoms.…”
Section: Introductionmentioning
confidence: 99%